Mechanisms of color formation in drug substance and mitigation strategies for the manufacture and storage of therapeutic proteins produced using mammalian cell culture. (November 2019) - Du, Cheng; Xu, Jianlin; Song, Hangtian; Tao, Li; Lewandowski, Angela; Ghose, Sanchayita; Borys, Michael C.; Li, Zheng Jian
Graphical abstract: Highlights: Protein color test is important for product release, comparability and stability. Atypical color can be introduced during most manufacturing steps and storage. Color assay methods, mechanisms and mitigation strategies are summarized. Color formation is mainly associated with Trp oxidation products and/or B12 . Major factors include iron, B12, light, temperature, aeration, and ROS. Abstract: Drug substance (DS) appearance is an important quality attribute that is tested before product release. Color variation in DS batches or color change during storage can be indicative of the presence of contaminants, impurities or degradation products and may be linked to the manufacturing process, DS formulation or the stability of the therapeutic proteins. Atypical DS color other than colorless or pale yellow has been recently observed and may result in rejected manufacturing batches and financial loss due to concerns on product quality and visually matching placebo in clinical trials. This review focuses on the origins of atypical color and changes in DS during manufacturing processes using mammalian cell culture and storage. The purposes here are to understand the link between changes in the DS color and various process parameters and to provide necessary information to our readers regarding product quality control strategies with respect to DS color.